Identifying and Ranking the Effective Factors in Improving the Quality of Student Dormitories by Comparing Analytical Network Process (ANP) and DEMATEL Methods. Case Study: Student Dormitories of the University of Qom - Kheyrollah Rahseparfard; Mohammad Moradi; Shohreh Teymoori (مدیریت مهندسی و رایانش نرم)
Student dormitories, as second homes for students, are of great importance. The purpose of the current research is to identify and rank the effective and important factors in providing an appropriate dormitory regarding the welfare of students. The effective factors are prioritized by comparing analytical network process and DEMATEL methods. This case study is conducted in dormitories of the University of Qom. In the current study, the data was collected through interviews and questionnaires filled out by officials and experts, according to which 17 criteria were selected as the basic criteria. Finally, 11 criteria were chosen as the key criteria by the experts. The results show that among the indicators and criteria studied, the management of dormitoy buildings and discipline are high priorities according to both methods. According to ANP analysis dormitory buildings accessing each other and according to DEMATEL analysis welfare services within the dormitory play the most important roles in improving the quality of a dormitory. Student dormitories, as second homes for students, are of great importance. The purpose of the current research is to identify and rank the effective and important factors in providing an appropriate dormitory regarding the welfare of students. The effective factors are prioritized by comparing analytical network process and DEMATEL methods. This case study is conducted in dormitories of the University of Qom. In the current study, the data was collected through interviews and questionnaires filled out by officials and experts, according to which 17 criteria were selected as the basic criteria. Finally, 11 criteria were chosen as the key criteria by the experts. The results show that among the indicators and criteria studied, the management of dormitoy buildings and discipline are high priorities according to both methods. According to ANP analysis dormitory buildings accessing each other and according to DEMATEL analysis welfare services within the dormitory play the most important roles in improving the quality of a dormitory.